A jurisprudential study: proving witchcraft in Africa - Mosaka, Tshepo Bogosiboile (2021)
Widespread incidents of mob violence that are associated with witchcraft pose significant risks towards African criminal process. The need to address the extent to which these incidents threaten the overall institutional legitimacy of African criminal process constitutes the principal motivation behind the project of this thesis. This thesis identifies three major sets of challenges that are complained about by African communities. These pertain to (1) the relevant institutional practices that are to be followed in witchcraft cases (institutional); (2) the legal meaning of witchcraft (material); and (3) the evidential heuristics or processes of proof that are required to prove the direct crime of witchcraft (probative). These institutional, material and probative challenges are then summarised into a single overall thesis question: how can the direct crime of witchcraft be proven in Africa?